2021
DOI: 10.3390/medicina57060519
|View full text |Cite
|
Sign up to set email alerts
|

Combined Systematic and MRI-US Fusion Prostate Biopsy Has the Highest Grading Accuracy When Compared to Final Pathology

Abstract: Background and objectives: Systematic prostate biopsy (SB) has a low Gleason group (GG) accuracy when compared to final pathology. This may negatively impact the inclusion of patients into specific risk groups and treatment choice. The aim of our study was to assess the GG accuracy of magnetic resonance imaging-ultrasound (MRI-US) fusion prostate biopsy. Materials and Methods: Of a cohort of minimally invasive radical prostatectomy (RP), we selected all patients who were diagnosed with prostate cancer (PCa) vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…CF identified four more cancer patients than SB, but the difference was not statistically significant ( p = 0.337). These results are consistent with the findings of other similar studies that found no difference in the overall cancer detection rate between the two methods [ 23 , 24 ]. However, our data showed an important 20% increase in clinically significant cancer detection (Gleason score ≥ 7 or ISUP score ≥ 2) by using cognitive fusion biopsy.…”
Section: Discussionsupporting
confidence: 93%
“…CF identified four more cancer patients than SB, but the difference was not statistically significant ( p = 0.337). These results are consistent with the findings of other similar studies that found no difference in the overall cancer detection rate between the two methods [ 23 , 24 ]. However, our data showed an important 20% increase in clinically significant cancer detection (Gleason score ≥ 7 or ISUP score ≥ 2) by using cognitive fusion biopsy.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that the cutoff values of T2 in the differential diagnosis of prostate transition zone and peripheral zone benign and malignant lesions were 0.840 and 0.796, respectively. For transition zone lesions with T2 ≤ 77 ms or T2 > 77 ms and peripheral zone lesions with T2 ≤ 81 ms or T2 > 81 ms, the single needle PCa biopsy positivity rates for TRUS/MRI fusion‐guided biopsy were significantly higher than those for SB ( p < 0.01), which is in agreement with the results of previous studies 20,21 . However, previous studies have shown conflicting views in terms of the overall detection rate of TRUS/MRI fusion‐guided biopsy and SB for PCa.…”
Section: Discussionsupporting
confidence: 91%
“…For transition zone lesions with T2 ≤ 77 ms or T2 > 77 ms and peripheral zone lesions with T2 ≤ 81 ms or T2 > 81 ms, the single needle PCa biopsy positivity rates for TRUS/MRI fusionguided biopsy were significantly higher than those for SB (p < 0.01), which is in agreement with the results of previous studies. 20,21 However, previous studies have shown conflicting views in terms of the overall detection rate of TRUS/MRI fusion-guided biopsy and SB for PCa. A previous study found that the value of fusion biopsy was greater, 6,22 while another showed that there was no significant difference in the PCa overall detection rate between the two methods.…”
mentioning
confidence: 99%
“…Limitations of a PM based on a cohort of patients whose pathological specimens were obtained by a surgical approach are the exclusion of patients who underwent radiotherapy, active surveillance, watchful waiting, metastatic patients or refusal of standard of care. However, strengths could be the presence of the histology of the whole prostate gland, as prostate a biopsy may downgrade prostate cancer [65].…”
Section: Discussionmentioning
confidence: 99%